Comparison of 2-octyl cyanoacrylate with prolene (4-0) sutures in extra oral wound closure - Padam Kumar; Alpana Katiyar; Ashish Tripathi; Asmita Gupta; Anubha Srivastav; Bhavneet S Uppal (Wolters Kluwer Medknow Publications, 2023)
Aim: To compare the healing following various maxillofacial incisions using 2-octyl cyanoacrylate (2-OCA) and prolene (4-0) sutures. Objective: To evaluate the complications and aesthetic outcome of the incision wounds after closure using 2-OCA and prolene (4-0) sutures. Materials and Methods: The patient undergoing an extraoral incision was evaluated for pain, inflammation, infection, dehiscence, scar, and surface texture. In Group I, 15 patient incisions were closed with 2-OCA and in Group II, 15 patient incisions were closed with prolene (4-0) suture. Result: A few patients experienced pain with Group I and then Group II, but infection, inflammation, and dehiscence were more in Group I than in Group II. Conclusion: A cosmetic outcome was higher in the cyanoacrylate group, and the surface texture was satisfying in the same group.